2005
DOI: 10.1063/1.2032600
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence in erbium doped amorphous silicon oxycarbide thin films

Abstract: Photoluminescence (PL) in Er-doped amorphous silicon oxycarbide (a-SiCxOy:Er) thin films, synthesized via thermal chemical vapor deposition, was investigated for carbon and oxygen concentrations in the range of 0–1.63. Intense room-temperature PL was observed at 1540 nm, with the PL intensity being dependent on the carbon and oxygen content. The strongest PL intensity was detected for a-SiC0.53O0.99:Er when pumped at 496.5 nm, with ∼20 times intensity enhancement as compared to a-SiO2:Er. Broadband excitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…26,28,32 Therefore, the formation of SiO 2 contents and Tb nanoclusters on the surface plays an important role in the enhancement of the PL activity of Tb 3þ ions, which is similar to the results from the Er-doped SiC materials. [2][3][4]9,49 To explain the ultraviolet photoluminescence from 4H-SiC nanocrystalline films, Fu et al 50 have used an extended quantum confinement/luminescence center model, which was first proposed by Qin. 51 Using this model, the PL of porous Si has been mainly divided into three parts, originating from the 4H-SiC core, the NIRs, and the SiO 2 surface, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26,28,32 Therefore, the formation of SiO 2 contents and Tb nanoclusters on the surface plays an important role in the enhancement of the PL activity of Tb 3þ ions, which is similar to the results from the Er-doped SiC materials. [2][3][4]9,49 To explain the ultraviolet photoluminescence from 4H-SiC nanocrystalline films, Fu et al 50 have used an extended quantum confinement/luminescence center model, which was first proposed by Qin. 51 Using this model, the PL of porous Si has been mainly divided into three parts, originating from the 4H-SiC core, the NIRs, and the SiO 2 surface, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] So far, the most frequently investigated RE element for the SiC materials is erbium (Er) because of its strong near-infrared luminescence at 1.54 mm, at which the transmission loss of silica-based optical fibers during optical communications is minimum. [2][3][4][5][6][7][8][9][10] Terbium (Tb) has frequently been used as dopant, because of its strong radiative intra-4f transitions in the green light region, which is very important to optoelectronic devices such as light-emitting diodes. [12][13][14][15][16][17][18][19][20] The photoluminescence (PL) properties of Tb-doped SiC(SiC:Tb) materials have been researched by several groups.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon oxycarbide is a class of non-crystalline and disordered ceramic materials which is usually synthesized by chemical methods including sol-gel [26], chemical vapor deposition [27], etc. To minimize the chemical residue and formation of free carbon, RFmagnetron co-sputtering of SiC and SiO 2 targets without direct heating of the substrate was used in the present study.…”
Section: Composition Of Sioc Filmsmentioning
confidence: 99%
“…Both XPS and FTIR data reveal the presence of significant amount of Si-C-O bonding component in the films. 11 Forming gas (H 2 5%, N 95%) annealing resulted in enhanced intensities for Si-H bonds (≤ 900 o C), but at 1100 o C these bonds are not detectable (inset in Fig 2(b)). Figure 3 shows the spectra of the matrix-related visible PL for a-SiC 0.36 O 1.40 sample with C content of 13.6 at.%, as functions of passivation annealing temperatures for two different gases (Ar, and forming gas).…”
Section: Methodsmentioning
confidence: 92%
“…9,10 To that end we have demonstrated that strong room-temperature infra red emission can be achieved in erbium (Er)-doped a-SiC x O y films at the commercially useful wavelength of 1540 nm under visible excitation. 11 Nevertheless, the matrix luminescence characteristics of such materials have not been revealed and the origin of the broadband ultraviolet/visible emission remains uncertain.…”
Section: Introductionmentioning
confidence: 99%